The art of the Delphi technique: highlighting its scientific merit - Emmerentia du Plessis; Susara P Human (AOSIS, 2007)
The initial use of the Delphi technique was forecasting in order to be able to plan ahead. Opsomming Die aanvanklike toepassing van die Delphi-tegniek was voorspelling met die doel om vooruit te kan beplan. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.